Catalytic oxidation of organic solvent vapour with Pt/Co3O4‐CeO2 supported on a honeycomb carrier. (1st October 2020) - Inoue, Kenichiro; Somekawa, Shoichi; Fujiwara, Hiroyuki; Kawami, Yoshimasa
Abstract: We supported Pt/Co3 O4 ‐CeO2 on a honeycomb carrier and examined the catalytic oxidation activity for organic solvent vapour. The support of platinum on Co3 O4 ‐CeO2 was not necessary if gas containing only ethyl acetate as organic solvent was treated. However, in gas containing both toluene and ethyl acetate, Pt/Co3 O4 ‐CeO2 showed higher activity than both Co3 O4 ‐CeO2 and commercial grade Pt/Al2 O3 . By first supporting Co3 O4 ‐CeO2 and then platinum on the honeycomb carrier, the platinum was concentrated more toward the surface of the catalyst and the activity increased. A test using sprayed paint thinner exhaust gas in a paint booth was also performed. Even when less platinum was utilized, by combining it with Co3 O4 ‐CeO2, the coexistent organic components of toluene, ethyl acetate, and butyl acetate, etc., in the exhaust gas were completely oxidized at 250°C.